Hydrologic evaluation of a poplar phytoextraction system. Issue 2 (28th January 2022) - Rabideau, Alan J.; Swensen, Katherine; Chen, Zixuan; Santiago-Collazo, Félix L.; Bronner, Colleen; Lowry, Christopher; Gnat, Richard; Lockwood, Terry
Abstract: This paper reports the results of a seven-year study of a phytoremediation system consisting of 349 hybrid poplars ( Populous deltoids x Populus nigra 'DN-21') that were emplaced to reduce the migration of impacted groundwater toward a nearby stream. For the relatively small tree stand, the achievement of hydraulic containment was challenged by several factors, including topographic constraints on tree placement, spatial heterogeneity in depth-to-groundwater, and lack of controls on surface runoff. However, the interpretation of measured diurnal water table fluctuations indicated substantial and increasing levels of groundwater extraction, consistent with poplar sap flow measurements collected during two growing seasons. The project also provided unique educational experiences for undergraduate and graduate students from multiple academic disciplines who participated in monitoring, site maintenance, and data interpretation. Novelty statement The paper adds to the limited literature on poplar-based phytoextraction of contaminated groundwater by describing a seven-year case study with detailed hydrologic measurements. Novel elements include (1) a very large data set of poplar sap flow measurements that provides insight into potential spatial and temporal variability, and (2) a detailed application of an under-utilized analytical tool (water table fluctuations) to evaluate hydraulic capture.